Prevalance of the tobacco alcohol and products use of a faculty of medicine students and risk factors - Avcı, Emine; İlhan, Mustafa Necmi; Civil, Emine Füsun; Özdemirkan, Tuğba; Bumin, Mehmet Ali (Journal of Dependence, 2014)
Objective: Smoking and alcohol use are common habits and an important public health problem. These habits, which is the biggest threats of our health becoming more common among young people and shrinking age of use day by day. In this study, evaluating prevalence of the tobacco, alcohol and products use of Gazi University Faculty of medicine students and risk factors are aimed.Methods: This study, which is cross-sectional-descriptive, is applied to 1003 students training in 2010-2011 education period at Gazi University Faculty of Medicine between 0428 February 2011 by questionnaire. The participation rate is 78,11%.Results: 53,8% of 1003 students is female , 46,2% is male. The lifetime prevalence of tobacco and products use is 37,6%, still tobacco and products use prevalence is 18,8%, lifetime alcohol and products use prevalence is 35,6%, still alcohol and products prevalence is 22,5% in this study. The prevalence of tobacco and product use is found significantly in students whose one of family members using tobacco and products than the students whose not (Odds Ratio:3,64, 95% confidence interval: 2,55-5,20). The prevalence of alcohol and product use is found significantly in students whose one of family members using alcohol and products than the students whose not (OR: 14,60 95% confidence interval: 9,94-21,44).Conclusion: Results of this study shows that faculty of medicine students need more education about tobacco, alcohol and products and interventions related to tobacco, alcohol and products use.
Keywords: Faculty of medicine students; tobacco and its products; alcohol and its products; prevalence of use; risk factors